(untitled) (Eurasian Scientific Herald, 2022)
This article discusses the types of reading in language teaching at the university. Depending on the target installation we distinguish the skimming, scanning, reading for detail. Mature ability to read involves both possession of all kinds of reading, and eases the transition from one of its kind to another depending on changes in the purpose of obtaining information from the text. And also states that these kinds of reading and developing their role in language teaching